RUMAH ADAT SASADU SEBAGAI SALURAN KOMUNIKASI KOMUNITAS SUKU SAHU - Rakhmat Rakhmat (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This study aims to explain that the function of the traditional Sasadu house is not only seen as a cultural phenomenon but can also be seen as a means of cultural communication owned by the Sahu Tribe community in West Halmahera Regency. The shape of this traditional house is rectangular which was built on the ground and does not have an insulating wall in the middle of the village on the side of the road so that everyone has easy access from various directions. The method used in this research is qualitative which explores the meaning of the Sasadu traditional house by using a communication approach. Data were obtained through interviews with informants who were selected in a purposive way or based on the criteria for the research objectives. The results of the study describe the existence of the Sasadu traditional house as a symbol that brings together people from various circles and becomes the glue of social relations. Every ornament in the Sasadu traditional house contains cultural messages that are full of meaning about the values of life that must be preserved by each generation so that apart from being a cultural heritage, the Sasadu traditional house also has a social and cultural communication function